Another twelve years: Hungarian newsreels and the invasion of Czechoslovakia in 1968 - Barkóczi, Janka; Justus Liebig University Giessen (My University, 2017)
During almost twelve years after the Soviet regime crushed the Hungarian Revolution, the Warsaw Pact allies invaded Czechoslovakia to put an end to the 1968 Prague Spring and the country s recent reformist trends. The Soviet troops were accompanied by military forces from Hungary, Poland, East Germany, and Bulgaria. Among many other serious consequences, this helped to preserve the long-term power of communist governments in the region.This paper examines the audio-visual and conceptual elements of the official newsreel series published by the Socialist state of the Hungarian People s Republic between May and October 1968, focusing on the representation of the intervention and the depiction of Czechoslovakia as an Eastern Bloc state. The essay argues that the official media of the regime led by János Kádár dealt with this topic in a highly sensitive way because of the possible echoes of the 1956 uprising. In the editorial guidelines of the newsreels, a special ritual manner was introduced to inform and orient the audiences according to the interests of the central propaganda.The techniques and forms of media argumentation are examined based on the collection of Hungarian newsreels of the Hungarian National Film Archive, using both qualitative and quantitative methods.
Keywords: 1968; Hungarian newsreels; invasion of Czechoslovakia; propaganda; visual argumentation; ddc:300